Proximat Test Of Making Innovative Herbal Tea As Prevention Of Non-Communicable Diseases Based On Laboratory Tests - RR. Sri Endang Pujiastuti; Sri Widiyati; Muflihah Isnawati Isnawati; Wanti; Agussalim Agussalim; Agnes Lia Renataa; Dhea Novita (Jurnal Riset Kesehatan, 2026)
The diversity of different soil types, climates, and topography in Indonesia creates ideal conditions for the growth of various plants and animals. Food diversity owned by Indonesia. Produced from each region certainly has many benefits for the community, for example the existence of local food can reduce dependence on food imports, improve the welfare of local farmers and maintain biodiversity. Some local ingredients that can be used as basic ingredients for making products that are beneficial to health include soybeans, tea from ant nests, tambi tea and Dayak onion tea. These ingredients have health-related benefits so various products can be developed from them. In addition, drinks can be made based on the mixing of these ingredients and obtain mineral content that is beneficial to the body. This study aims to determine the content of the innovation of herbal tea test results. This research method is carried out by conducting laboratory tests on food ingredients that will be used as processed products. The laboratory test carried out is a proximate test that measures water content, protein content, fat content, ash content and carbohydrate content of foodstuffs. The results of antioxidant tests on healthy tea variations showed that the IC50 value in tambi tea was 4.4251, anthill tea was 24.5073, MSME soy milk was 62.7083 and soybean powder was 42.6356. Variations of tea and soy milk have antioxidant content and healthy tea innovations have protein, fat, ash content, water and carbohydrates. These various ingredients have their own benefits for the body.Â Â